2011
DOI: 10.1136/jfprhc-2011-0079
|View full text |Cite
|
Sign up to set email alerts
|

Contraception use and unplanned pregnancies among injection drug-using women in St Petersburg, Russia: Table 1

Abstract: Background This cross-sectional study estimated the prevalence of contraceptive methods and investigated whether abortion rates influence contraceptive behaviour among injection drug-using (IDU) women in St Petersburg, Russia. Methodology A self-administered questionnaire of behaviour in the last 3 months was applied to a convenient sample of IDU women. Results Of 80 sexually active participants, 67% had had an abortion. No participant reported using hormonal contraceptives or intrauterine devices (IUDs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 52 publications
4
21
3
Order By: Relevance
“…This is one of few clinical Brazilian studies undertaken in a clinical setting to evaluate abortion prevalence in a large drug user sample. Abortion is a method used to prevent births in many developing countries 21 including in Brazil 6,35 and rates remain high around the world 13,36,37,38 . The association between abortion and substance use is a public health problem of great magnitude which makes a substantial contribution to maternal morbidity and mortality 1,2,3,39 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is one of few clinical Brazilian studies undertaken in a clinical setting to evaluate abortion prevalence in a large drug user sample. Abortion is a method used to prevent births in many developing countries 21 including in Brazil 6,35 and rates remain high around the world 13,36,37,38 . The association between abortion and substance use is a public health problem of great magnitude which makes a substantial contribution to maternal morbidity and mortality 1,2,3,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The SADD is a scale consisted of 15 questions related to the alcohol dependence severity, classified on a scale from 0 to 20, and scored as follows: mild (0-9), moderate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (≥ 20). The Brazilian version and the original English version of the SADD are highly correlated and the coefficient of internal consistency is 0.79 33 .…”
Section: • Short Alcohol Dependence Data (Sadd)mentioning
confidence: 99%
See 2 more Smart Citations
“…[140][141][142] High rates of abortion have been reported among women who use drugs, some of whom are also sex workers, however, reduction in abortion-related risks and integration of family planning and post-abortion care in this population has not adequately been documented. [143][144][145] Fertility-related assessments prior to pregnancy in this population are limited, although studies focused on women living with HIV in Canada, including women who use drugs, suggested that drug use did not affect fertility intentions. 146 Evidence-based and human rightsaffirming interventions are needed at this time when certain programming efforts incentivize contraceptive use or sterilization among women who use drugs.…”
Section: Women Who Use Drugsmentioning
confidence: 97%